A inconstitucionalidade das tributações exclusiva na fonte e definitiva frente ao regime jurídico constitucional do imposto sobre a renda das pessoas físicas - Quaresma Neto, Leônidas Barbosa (2022)
The income tax has as constitutional materiality the available asset increase verified over a period of time. There are several principles and limits imposed in our Constitution regarding the collection of this tax. However, we see a gap between the ordinary legislation and these constitutional precepts, especially with regard to exclusive withholding at the source and definitive taxation. This paper seeks to analyze the unconstitutionalities of the exclusive withholding and definitive taxation against the constitutional concept of income, illuminated by the constitutional principles of generality, universality and progressiveness. It is concluded that such regimes violate the concept, as well as the criteria of progressivity, universality and generality